Impact of Social Capital on Environmental Governance Efficiency—Behavior of Guangdong, China - Zhang, Shujian; Gu, Zhijun (Frontiers in Energy Research, 2021)
The main purpose of this article is to investigate the impact of social capital level on environmental governance efficiency in economically developed areas. We choose China’s richest province Guangdong. Compared with other Chinese provinces, Guangdong’s local governments are in better fiscal status, and they can allocate environmental spending in line with the trend of gross domestic product per capita. We want to observe the important factors related to social cognition other than capital investment to gain a more profound influence on the efficiency of local environmental governance. This article assumes that the degree of local social capital will have a great positive impact on the efficiency of regional environmental governance. Super-efficiency slacks-based measure method of data envelopment analysis is adopted to calculate the environmental governance efficiency by considering the expected output and the nonexpected output. Then, short-panel regression was used to analyze the relationship between social capital and environmental governance efficiency. Through an empirical analysis of urban panel data of Guangdong province from 2001 to 2019, it is found that the degree of social capital does have a significant positive impact on the efficiency of local environmental governance. After the research conclusion, we propose some policy suggestions to local governments.